English grammar e-module development using ADDIE model - Adiningtyas, Cyntya Niken; Rufii, Rufii; Waluyo, Djoko Adi (Jurnal Mantik, 2024)
One of the aspects in the process of English language learning is to learn Grammar. Grammar is a set of rules used to organize language. In EFL context, unlike Bahasa Indonesia, English has sixteen different types of rules which are used based on function and time. In the English learning process, learning resources are essential component for teachers and students. One of the learning resources that can be used by teacher and students in this technological era is E-module. Thus, the aim of this research is to develop a teaching material adopting ADDIE model that can help students to comprehend the English structure. ADDIE model consists of 1) Analysis; 2) Design; 3) Development & Implementation; 4) Evaluation; 5) Final Product. The subject of this research was carried out in 1 class with 28 students, as well as an English teacher. Research and Development (R&D) research method was used in this research. In the process of developing the product, it was validated by material expert and media expert first, before being tested in classroom learning condition. The results showed that the development of English grammar E-module is valid and can be used in learning process. It showed by the results of validation scores which carried out by the experts. Other results are also shown in teacher response questionnaire which the effectiveness is in “high” category and the students response questionnaire showed that English grammar E-module “practical” in category. The subject of this research was carried out in 1 class with 28 students, as well as an English teacher